Higher Order Thinking Reading Strategies: An Alternative to Improve Students’ Reading Comprehension in the Indonesian EFL Context - Fatimah Fatimah (Alphabet: A Biannual Academic Journal on Language, Literary, and Cultural Studies, 2021)
Teaching reading in English as a foreign language in Indonesia is challenging since it is not only to enable the students to comprehend a reading text, but also to enable them to relate their understanding of the text to their real life. This paper proposes an alternative to English teachers in Indonesia on how to employ higher order thinking reading strategies to achieve the objective. To begin with, the writer discusses reading and reading interest in Indonesia. The writer then reviews higher order thinking reading strategies, teaching strategies related to higher order thinking skills, and graphic organizers. In the end, the writer expects that Indonesian teachers employ higher order thinking reading strategies to encourage their students to use their knowledge and life experience while reading a particular text so that they will be interested in reading and comprehend the text better.